2021
DOI: 10.1021/acsnano.1c10112
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Noble Metal–Metalloid/Nonmetal Alloy Nanomaterials: Designing Highly Efficient Catalysts

Abstract: Mesoporous metals have received increasing attention in catalysis and related applications because of their novel physicochemical properties and functional geometric features. Control of multicomponent compositions and crystalline structures of mesoporous metals is critical for their applications. Recently, mesoporous metals have gradually expanded from traditional metal–metal alloys to metal–metalloid/nonmetal alloys with random solids and/or ordered intermetallics. As new, highly efficient nanocatalysts, mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 81 publications
0
26
0
Order By: Relevance
“…37 In addition, by adding an amphiphilic surfactant template, this aqueous synthesis involving DMAB can be further extended to construct different nanostructured Pd−B alloys such as nanospheres, nanowires, nanopillars, and so on. 52,56,59,60 To increase the B-doping content in Pd−B alloys, Chen at al. 40 used N, N-dimethylformamide (DMF) as the solvent to synthesize Pd−B nanocrystals using NaBH 4 as the reductant and B source.…”
Section: Synthesis Of B-doped Pgm Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 In addition, by adding an amphiphilic surfactant template, this aqueous synthesis involving DMAB can be further extended to construct different nanostructured Pd−B alloys such as nanospheres, nanowires, nanopillars, and so on. 52,56,59,60 To increase the B-doping content in Pd−B alloys, Chen at al. 40 used N, N-dimethylformamide (DMF) as the solvent to synthesize Pd−B nanocrystals using NaBH 4 as the reductant and B source.…”
Section: Synthesis Of B-doped Pgm Catalystsmentioning
confidence: 99%
“…Lowering the reaction temperature, increasing the mole ratio of DMAB or NaBH 4 to a Pd­(II) precursor, and extending the reaction time favor an increased B-doping level. ,,, In fact, under otherwise similar conditions, DMAB and NaBH 4 yield B-doping levels of ∼6.7 and 2.7 atom % in Pd nanoparticles, respectively, in aqueous-phase synthesis . In addition, by adding an amphiphilic surfactant template, this aqueous synthesis involving DMAB can be further extended to construct different nanostructured Pd–B alloys such as nanospheres, nanowires, nanopillars, and so on. ,,, …”
Section: Geometric and Electronic Structures Of B-doped Pgm Catalystsmentioning
confidence: 99%
“…Besides morphological advantages, the incorporation of other elements into metal nanostructures has been extensively investigated to enhance their catalytic activity and durability for different reactions 25–28 . Recently, metal–nonmetal nanostructures, by incorporating nonmetallic elements like P, B, H, and S in metal nanostructures, have emerged as a promising candidate for the enhancement of electrocatalytic performance 29–33 . Metal phosphides (M–P) like Pd–P, 34 Co–P, 35 Rh–P, 36 and Ni–P 37 have attracted tremendous interest because of their outstanding performance in different electrocatalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] Recently, metal-nonmetal nanostructures, by incorporating nonmetallic elements like P, B, H, and S in metal nanostructures, have emerged as a promising candidate for the enhancement of electrocatalytic performance. [29][30][31][32][33] Metal phosphides (M-P) like Pd-P, 34 Co-P, 35 Rh-P, 36 and Ni-P 37 have attracted tremendous interest because of their outstanding performance in different electrocatalytic reactions. For instance, Luo et al reported that Pd-P NCs revealed interesting electrocatalytic HER and oxygen evolution reaction activities.…”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous metals are a new type of nanostructured materials, whose nanoscale crystalline skeletons are solidly surrounded by abundant 2–50 nm mesopores. Mesoporous metals have been recognized as second-generation mesoporous materials because of their intrinsic physiochemical properties, including high porosities, larger surface areas, abundant active sites, and better electroconductivities. They have been widely applied in catalysis, electrocatalysis, biosensors, and bioimaging, which are rarely achieved by other structures and/or compositions.…”
mentioning
confidence: 99%